Variaciones genéricas del Anathematikón en las Cartas de Filóstrato (Minerva, 2019)
On the basis of the list established by Cairns in order to classify the primary and secundary elements which constitute the anathematikón, in this paper the author analyzes the peculiar literary innovation that involves the modification –at times inversion– of those elements in some letters of the Philostratus’ “the Elder” epistolary corpus.